Peningkatan Kesejahteraan Rumah Tangga melalui Pembuatan Sabun Cuci Piring Berbasis Ampas Kopi Sebagai Bahan Alternatif Bagi Masyarakat Desa Kebonan Kabupaten Boyolali - Maghfiroh, Jauza Nurul; Anam, Khoiril; Adi, Andreas Septian; Jatmika, Yassir (Jurnal Bina Desa, 2025)
Coffee grounds are a by-product of coffee shops and household consumption which often become organic waste that is not fully utilized. One interesting solution is to use coffee grounds as raw material for value-added products, such as dishwashing soap. The aim of this service is that the UNNES Giat 6 Kebonan Village Team provides alternative solutions in the form of education and assistance regarding the use of coffee grounds in environmentally friendly dishwashing soap to improve household welfare and strengthen the local economy. The implementation of this activity involved various elements, such as Active 8 UNNES Students, posyandu cadres and the surrounding community. This service uses direct observation methods with implementation methods in the form of education and assistance to the Kebonan Village Hall service location by providing assistance in making dish soap from coffee grounds. The research results show that coffee grounds can be an effective alternative ingredient in making dishwashing soap that is environmentally friendly and saves household expenses. The resulting soap is proven to be effective in cleaning kitchen equipment and reducing negative impacts on the environment.